Radiotherapy in pelvic malignancies at King Chulalongkorn Memorial Hospital, Thai Red Cross Society - Arphasetthasakul, Wisan; Muangkhamporn , Kanokporn; Huangnam , Sajjaporn; Kumkhwao, Jumnong (The Thai Journal of Radiological Technology, 2024)
Radiotherapy involves treating malignant cells using beams of intense energy to destroy cancer cells, making precision critical at every step. This process begins with patient preparation, treatment simulation, irradiation, positioning, and the use of appropriate immobilization techniques. However, variations can occur, such as discrepancies between patient positioning during simulation and actual treatment. For patients with pelvic malignancies, maintaining a full bladder and an empty rectum is essential to minimize side effects on surrounding normal organs. Controlling the volume of these organs is challenging, so image verification is necessary before treatment, using methods like EPID (Electronic Portal Imaging Device) or CBCT (Cone Beam Computed Tomography). n brachytherapy, imaging is particularly crucial. At KCMH, both pre- and post-treatment MRI imaging is performed to aid doctors in evaluating and planning treatment. In radiotherapy, acquiring images is a key responsibility of radiologic technologists. Therefore, this article is intended for those interested in enhancing their knowledge of pelvic cancer treatment with radiotherapy at King Chulalongkorn Memorial Hospital, Thai Red Cross Society.